Communicating Circular Design: A ReSuit case study of embedding knowledge of circularity from design to wholesale to shop assistant - Hall, Cathryn Anneka; Ravnbøl, Kristoffer; Pedersen, Julie (Proceedings of the 6th Product Lifetimes and the Environment Conference (PLATE2025), 2025)
This paper explores how garments, which have had circular design embedded within them, can be communicated in industry from the design department to wholesale, shop managers/assistants and lastly the consumer. The research was situated within the ReSuit project as a case study and was a collaboration between design researchers at Kolding School of Design, anthropologists at Behave Green and industry partner Bestseller. The research was conducted in two parts. Firstly, it investigated, through interviews, how designers communicate circular/sustainable design to wholesale. Secondly, a parallel study used interviews to investigate the communication from shop assistants to customers. The findings show that designers find it complex to communicate sustainability and circularity embedded within designs to wholesale, and the information regarding these topics gets diluted as the overall information burden is seen as too overwhelming. It was also found that shop floor staff were not equipped to guide customers towards sustainable/circular choices and that the customers knowledge, though interested, is lacking. However, it also demonstrates a range of methods that brands could draw on to aid communication, namely overview presentations supplemented with physical visuals, diagrams, first-hand experience or changing the presentation location. Furthermore, aids were suggested, such as mini guides, QR codes and websites. This paper proposes that, to communicate outwardly, brands should first look inward, to educate/upskill their sales teams (Business-to-Business and Business-to-Customer) with fundamental sustainable/circular knowledge. The paper concludes that salespeople have the potential to play a pivotal role in the transition to a circular economy.